PREDICTION OF THE BENDING STRENGTH USING RESPONSE SURFACE METHODOLOGY - ahmad kamely, mohamad; Sachlan, Ermansyah; Sivarao, Subramonian (Curran Associates, Inc, 57 Morehouse Lane ,Red Hook, NY 12571 USA, 2011)
Response surface methodology (RSM) is a collection of data that used mathematical and statistical technique to model and analyze problem in which the response (output) are influenced by several factors (parameters). In this study, a mathematical model was developed using RSM to predict the bending strength of aluminium alloys 6064 weldment. Data analysis is performed using Design Expert 7.03. The adequacy of the models has been attempted by using analysis-ofvariance (ANOVA) technique. Experimental results showed that model has 90% confidence level and the model can be use to predict the bending strength of Aluminium alloys 6064 weldments within the range of parameter considered in this investigation.